Complete physics for Cambridge IGCSE - Pople, Stephen (New York : Oxford University Press, 2010)
This second edition provides full coverage of the most recent Cambridge IGCSE syllabus in a highly illustrative and accessible way. It also comes with a free CD, including additional exam style questions, interactive exercises and revision tips. Fully endorsed by Cambridge International Examinations.
Includes Reference, Answers, and Index
Keywords: Physics -- Examinations; Physics -- Examinations -- Study guide